2020
DOI: 10.1108/cg-05-2020-0199
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the links between executive compensation structure and firm performance: evidence from the Brazilian market

Abstract: Purpose This study aims to investigate how different executive compensation structures were related to the performance of firms. Design/methodology/approach This study was based on a sample of companies with the highest standards of corporate governance listed on the Brazilian Stock Exchange. We adopted the multiple correspondence analysis followed by the hierarchical cluster analysis to propose a typology defined by fixed and variable components of the executive compensation and multiple firm performance in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…Concluding the above discussion, it is stated that corporate governance mitigates the agency’s problem by restricting the entrenched management behavior, having a more significant number of independent and fiscal advisors, thus preventing the wealth of investor’s expropriation. Thus, the idle liquid assets would not be accumulated, affecting the company’s market value in the articulation of preparing it to go public (Dias et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Concluding the above discussion, it is stated that corporate governance mitigates the agency’s problem by restricting the entrenched management behavior, having a more significant number of independent and fiscal advisors, thus preventing the wealth of investor’s expropriation. Thus, the idle liquid assets would not be accumulated, affecting the company’s market value in the articulation of preparing it to go public (Dias et al , 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Stakeholders are not only the shareholders and employees of the enterprise but also the customers whose interests need to be taken into account. Moreover, research findings on the relationship between CSR and consumer loyalty remain mixed and divergent (Walsh and Bartikowski, 2013;Kim et al, 2017;Pe ´rez and Del Bosque, 2017;Hur et al, 2018;Raza et al, 2018;Dias et al, 2020;Farrukh et al, 2020;). Raza et al (2020aRaza et al ( , 2020b, suggest that CSR does not influence customer loyalty, which is in contradiction with established work in developed countries.…”
Section: Corporate Social Responsibility Performance and Customer Loyaltymentioning
confidence: 99%
“…The level of compensation offered to chief executive officers (CEOs) and the relationship between executive pay and companies' financial performance are among the issues that the corporate governance literature deals with the most often. This topic was discussed in the last several decades (Jensen & Murphy, 1990;Mäkinen, 2005;Kato & Kubo, 2006;Brick et al, 2006;Iwu-Egwuonwu, 2010;Ozkan, 2011;Raithatha & Komera, 2016;Amarou & Bensaid, 2017;Yamina & Mohamed, 2017) as well as in recent years (Le et al, 2020;Lin & Shi, 2020;Dias et al, 2020;Amewu & Alagidede, 2021;Cui et al, 2021;Ding & Chea, 2021;Wang et al, 2021;Chen & Hassan, 2022;Kayani & Gan, 2022). Nonetheless, some authors have demonstrated empirically that the relationship between executive compensation and financial performance is significant and positive, while others have not found such a relationship at all.…”
Section: Introductionmentioning
confidence: 99%